2020
DOI: 10.3390/nu12082218
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Statins and Omega-3 Supplementation on Cardiovascular Events: Meta-Analysis and Network Meta-Analysis of 63 Randomized Controlled Trials Including 264,516 Participants

Abstract: Statins and omega-3 supplementation have been recommended for cardiovascular disease prevention, but comparative effects have not been investigated. This study aimed to summarize current evidence of the effect of statins and omega-3 supplementation on cardiovascular events. A meta-analysis and a network meta-analysis of 63 randomized controlled trials were used to calculate pooled relative risks (RRs) and 95% confidence intervals (CIs) for the effects of specific statins and omega-3 supplementation compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 103 publications
1
9
0
Order By: Relevance
“…Most large RCT v. placebo also support a CHD protective effect in secondary prevention with about a 20 % decrease in CHD death and 30 % decrease in CHD events with doses of EPA þ DHA ≥ 900 mg/d in secondary CHD prevention. This is confirmed by several recent meta-analyses (118,(120)(121)(122)(123)(124)(125)(126) . Negative studies for some of them can be criticised for their lack of power and/or by the use of OO as a placebo.…”
Section: Meta-analysessupporting
confidence: 65%
See 1 more Smart Citation
“…Most large RCT v. placebo also support a CHD protective effect in secondary prevention with about a 20 % decrease in CHD death and 30 % decrease in CHD events with doses of EPA þ DHA ≥ 900 mg/d in secondary CHD prevention. This is confirmed by several recent meta-analyses (118,(120)(121)(122)(123)(124)(125)(126) . Negative studies for some of them can be criticised for their lack of power and/or by the use of OO as a placebo.…”
Section: Meta-analysessupporting
confidence: 65%
“…EPA þ statin resulted in an 18 % reduction in the incidence of MACE (RR 0•78; 95 % CI 0•65, 0•93; P<0•01) and a 30 % reduction in MI (RR 0•71; 95 % CI 0•61, 0•82; P<0•01) as compared with statin alone. Hoang & Kim (122) , in 2020, performed a meta-analysis of eighteen RCT using LC n-3 supplements for at least 1 year. They decreased CHD by 10 % (RR 0•90; 95 % CI 0•84, 0•96) and MI by 12 % (RR 0•88; 95 % CI 0•83, 0•94).…”
Section: Meta-analysesmentioning
confidence: 99%
“…Statins exhibit pleiotropic effects, being able to improve vascular endothelial function, antiinflammatory, antioxidant, immunomodulatory and antibacterial effects [36][37][38][39][40]. For this reason, statins have been extensively applied in T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few clinical studies have shown the effectiveness of n-3 PUFAs in high-risk patients, the benefit of n-3 PUFAs in the prevention of ASCVD remains controversial [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. For primary prevention, a study of cardiovascular events in diabetes (ASCEND) [ 43 ] and a long-term outcomes study to assess STatin Residual Risk Reduction With EpaNova in HiGh Cardiovascular Risk PatienTs With Hypertriglyceridemia (STRENGTH) [ 44 ] failed to show a significant reduction in ASCVD by n-3 PUFA formulation in high risk patients.…”
Section: Discussionmentioning
confidence: 99%